Pembelajaran Bahasa Arab Melalui Channel Youtube Arab Podcast - Ida Alinda Fathonah; Abdul Majid; Chairani Astina (Journal of Student Research, 2024)
In this modern era, technology plays a crucial role in facilitating learning and enhancing understanding of academic material. This study focuses on Arabic language learning through the YouTube channel Arab Podcast, particularly on the video content of the book "Takalam Al-Arabiyah Volume 1". The research aims to provide a comprehensive overview of Arabic language learning through this channel, to understand the concept of content presentation, and to assist individuals in learning Arabic more easily. The study employed a qualitative literature review method with content analysis and discourse analysis techniques. Findings indicate that Arab Podcast not only serves as an effective learning resource but also fosters an active learning community through interactions in the comment section and positive feedback. By employing the As-Sam’iyah As-Syafahiyah presentation method and communicative approach supported by direct methods, systematically presented videos help learners understand and apply the material effectively, thereby creating an interactive and supportive learning community.